Earth called - Cast, P. C. (New York : Wednesday Books, 2023)
"In this last installment of the Tales of a New World series, love and goodness are put to the ultimate test as gods, humans, and animals come together to save everything they hold dear"--
Ages 12-18.
Keywords: Fantasy fiction; Alliances -- Fiction; Healers -- Fiction; Imaginary wars and battles -- Fiction; Magic -- Fiction; Fantasy fiction; Novels